What About the Girls? Exploring the Gender Data Gap in Talent Development - Curran, Orlaith; MacNamara, Aine; Passmore, David (Frontiers in Sports and Active Living, 2019)
Although there is an extensive literature about talent development, the lack of data pertaining to females is problematic. Indeed, the gender data gap can be seen in practically all domains including sport and exercise medicine. Evidence-based practice is the systematic reviewing of the best evidence in order to make informed choices about practice. Unfortunately, it may be that the data collected in sport is typically about male experiences, and not female; a rather unfortunate omission given that approximately half of the population is made up of women. When female athletes are underrepresented in research there are issues when making inferences about data collected in male dominated research domains to inform practice and policy for female athletes. In parallel, female sport participation is continually increasing worldwide. Recognising the importance of evidence-based practice in driving policy and practice, and reflecting the gender data gap that is a consistent feature of (almost) all other domains, we were interested in examining whether a gender data gap exists in talent development research. The results suggest that a gender data gap exists in talent development research across all topics. Youth athlete development pathways may be failing to recognise the development requirements of females, particularly where female sports may be borrowing systems that are perceived to work for their male counterparts. In order to ensure robust evidence based practice in female youth sport there is a need to increase the visibility of female athletes in talent development literature.